EXPERIENCE-VALUE ORIENTED MANAGEMENT STRATEGIES FOR HEALTH CHECKUPS IN TAIWAN MEDICAL CENTERS: Received: 12th January 2026, Revised: 13th January 2026, 14th January 2026, Accepted: 15th January 2026, Date of Publication: 16th March 2026 - Ching-Kuo Wei (PEOPLE: International Journal of Social Sciences, 2026)
The study aims to analyze the consumption behavior and the mechanism of loyalty formation among customers at high-end health management centers affiliated with medical centers in Taiwan. It focuses on how service quality, customer satisfaction, and brand image interact to influence loyalty in a highly competitive market. A survey method was adopted, targeting high-end health checkup customers at medical centers in Taiwan. From June to November 2024, 500 questionnaires were distributed, resulting in 446 valid samples. The questionnaire was reviewed by experts for expert validity, and the data met the required standards after reliability analysis. Demographic Impact: Age significantly affects service quality, satisfaction, brand image, and loyalty. Specifically, the 31-40 age group scored higher than the 21-30 group across multiple dimensions. Additionally, customers with lower education levels exhibited higher loyalty. Correlation Analysis: All main variables (quality, satisfaction, brand image, and loyalty) showed significant positive correlations. Regression Analysis: The model explained 55.4% of the variance in loyalty. "Brand Image" was the most critical factor (β = .428), followed by "Customer Satisfaction" (β = .306). Notably, "Service Quality" did not have a significant direct impact on loyalty. Loyalty in high-end health checkups is primarily driven by "experiential value" and "brand trust" rather than basic medical quality, which is now taken for granted by customers.Healthcare institutions should strengthen brand positioning and differentiate themselves through professional imagery and high-end facilities. They should optimize the customer experience process (e.g., managing waiting times) and cater to the specific needs of different groups. Ultimately, providers must shift from a "quality-oriented" approach to an "experience and value-oriented" management model.